Jay : ninja of lightning - Farshtey, Greg (Scholastic, 2012)
Sensei Wu must teach the Ninjago warriors the ancient art of spinjitzu in order to defeat Lord Garmadon, but first the ninja Jay, whose sense of humor is strong even in battle, must learn when it is the right time to be serious.